The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/mice.12065
|View full text |Cite
|
Sign up to set email alerts
|

Practical Visualization of Local Vibration Data Collected over Large Concrete Elements

Abstract: In this article, an original multidimensional presentation format for nondestructive evaluation point test spectral data is proposed. Time domain signals from air‐coupled impact‐echo (IE) tests are transformed into the frequency domain and arranged along x and y coordinates of the tested surface to give a 3‐D data set volume. Spectral amplitude is indicated by gray scale, giving rise to a “fourth” dimension of information within the data volume. This presentation, which stacks data in both spatial and spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Detailed theory can be found in [12]. Oh & Popovics [13,14] found that the flexural vibration frequency for significant near-surface delaminations (greater than 160 mm x 160 mm) falls below 6 kHz in most cases. In contrast, the thickness stretch resonance frequency does not usually fall below 6 kHz because the plate thickness, for example of a bridge deck, is normally in the range of (20 to 30) cm.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…Detailed theory can be found in [12]. Oh & Popovics [13,14] found that the flexural vibration frequency for significant near-surface delaminations (greater than 160 mm x 160 mm) falls below 6 kHz in most cases. In contrast, the thickness stretch resonance frequency does not usually fall below 6 kHz because the plate thickness, for example of a bridge deck, is normally in the range of (20 to 30) cm.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…These distances are not sufficient to detect smaller defects. Contactless system ACIE provides the ability to implement research on denser grid, as well as the duration of each test ACIE is much shorter [7], which provides greater accuracy.…”
Section: Impact Echo and Air-coupled Impact-echo Methods Of Ndtmentioning
confidence: 99%
“…Application of proposed data of manipulation and visualization technique to IE data collected from two different reinforced concrete samples demonstrates improved near-surface delamination detection as compared with conventional data formats [7].…”
Section: Software Methodsmentioning
confidence: 99%
“…Detailed theory can be found in [12]. Oh & Popovics [13,14] found that the flexural vibration frequency for significant near-surface delaminations (greater than 160 mm× 160 mm) falls below 6 kHz in most cases. In contrast, the thickness stretch resonance frequency does not usually fall below 6 kHz because the plate thickness, for example, of a bridge deck, usually is in the range of (20 to 30) cm.…”
Section: Impact Echomentioning
confidence: 99%
“…Fig 14. Mean FFT of 14 signals recorded by PCB 352C33 accelerometer (Acc), PCB 378B02 microphone (Mic), and laser Doppler vibrometer (LDV) using the surface test configuration.…”
mentioning
confidence: 99%